IDENTIFIKASI TINGKAT KESUBURAN TANAH DAN SIFAT KIMIA TANAH PADA LAHAN PEMBUDIDAYAAN SAYUR-SAYURAN DI KELURAHAN REWARANGGA SELATAN - Abraham Banggo; Charly Mutiara; Philipus Nerius Supardi (Agriculture Faculty of Flores University, 2021)
Excessive use of inorganic fertilizers and intensive tillage can cause changes in chemical properties and soil fertility. This study aims to determine the chemical properties of the soil and the level of soil fertility on land that cultivates vegetables. The research was conducted in Rewarangga Selatan Village, Ende Regency. This research was conducted using a survey method, by taking soil samples by composite methods on spinach, mustard and kale vegetables. The variables observed were soil pH, C-Organic, P2O5, K2O, CEC, and KB. These variables were analyzed for soil chemical properties and then matched using soil chemical criteria and soil fertility from the Bogor Soil Research Center. The results showed that the soil chemical criteria were soil pH in the acidic to very acidic category (4.0–5.0) , moderate C-Organic (2.03% – 2.37%), very high P2O5 (39.53 ppm – 48.90 ppm), very high K2O (1.01 me/100gr – 1.24 me/100gr), very high CEC (40.11 me/100gr – 40.33 me/100gr), and very high KB (82 ,11% - 86.76%) . While the criteria for soil fertility in the cultivation of vegetables are moderate.